The process of population ageing in countries of the Visegrad Group (V4) - Káčerová, Marcela; Ondačková, Jana (ERDKUNDE, 2015)
The study presents a comprehensive analysis of the issue of population ageing in the countries of the Visegrad Group (V4). Unprecedented changes in the populations’ age structure are examined and described within the broader context of social, economic and demographic developments in Europe. By comparing the demographic behaviour in the examined countries, the study provides new and relevant findings about inherent differences between the individual countries as well as within individual regions (NUTS 2).A comprehensive approach to study of the issue was maintained through the use of a broad range of methods. The temporal analysis was conducted by means of Rosset’s classification and the Ossan triangle. The time period for examining the demographic changes was from 1960 to 2012. The Ossan triangle and cartographic analysis facilitate the comparison of age structure at the regional level. The study identifies the degree of population ageing, the key factors at work, and the internal structure of the phenomenon within the studied areas. Right from the onset of population ageing in the Czech Republic and Hungary, these countries have been converging to levels typical for Western European counterparts. A delayed onset of population ageing has been typical for the more conservative countries of Slovakia and Poland. Over the years in this study, several factors have affected population ageing – from economic and social developments to the emergence of new ideological currents as well as the absence of population policies. However, the internal structure of ageing within the examined countries has not been homogeneous. In North Western Czech Republic, Northern Hungary, the Northern Great Plain of Hungary, and Central and Eastern Slovakia, a relatively early timing of fertility is considered as standard due to the different ethnic, religious or educational characteristics of the population as well as weaker economies in these regions. On the other hand, Western Slovakia, Prague, South Eastern Central Hungary and Central Transdanubia have become centers of the newer ideological currents. Eastern Slovakia, Northern Hungary, the Northern Great Plain and the eastern part of Poland, with underdeveloped infrastructure and capital, have quickly become an ageing eastern periphery of the European Union.